2023
DOI: 10.4271/2023-01-1452
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Modification on the Hybrid Ice Protection Systems Performances

Abstract: <div class="section abstract"><div class="htmlview paragraph">The formation of ice can be very detrimental to flight safety, since the ice accumulated on the surfaces of the aircraft can alter both the aerodynamics and the weight, leading in some cases to catastrophic lift reductions. Traditional active Ice Protection Systems (IPS) require high energy to work, add on weight to the aircraft and complexity to the manufacturing. On the other hand, the use of passive IPS, such as superhydrophobic/iceph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…However, for future sustainable aviation, low-energy-demanding IPS must be designed. Hybrid IPSs, which combine active IPSs with passive superhydrophobic/icephobic coatings, able to prevent, delay, and/or reduce the ice accretion, might represent a valuable solution, reducing the energy consumption and the CO 2 emissions [1][2][3][4][5]. Recently, Morita et al [6] found that the combination of icephobic coatings with electrothermal heating IPS reduces the energy requirements by more than 70% at LWC of 0.6 g/m 3 and a median volume diameter (MVD) of 15 µm at 75 m/s.…”
mentioning
confidence: 99%
“…However, for future sustainable aviation, low-energy-demanding IPS must be designed. Hybrid IPSs, which combine active IPSs with passive superhydrophobic/icephobic coatings, able to prevent, delay, and/or reduce the ice accretion, might represent a valuable solution, reducing the energy consumption and the CO 2 emissions [1][2][3][4][5]. Recently, Morita et al [6] found that the combination of icephobic coatings with electrothermal heating IPS reduces the energy requirements by more than 70% at LWC of 0.6 g/m 3 and a median volume diameter (MVD) of 15 µm at 75 m/s.…”
mentioning
confidence: 99%